Avaliação da adesividade de diferentes cimentos usados na cimentação de pinos de fibra de vidro - Ibrahim, Mariam Tansi (2015)
The success of endodontic treatment depends on the shaping of the root canal system with the proper technique using irrigation during preparation, to obtain a root canal filling, with the completion of endodontic treatment have to function the tooth such as restoration or permanente prosthesis we market the root intra pins, among them we have the pin glass fiber, this pin and made into single session with resin cement self condition glass ionomer cement, respecting the indications and contraindications of each. The scope of this study was to evaluate the adhesive strength pin reinforced by fibers(DT Light Post,Bisco, EUA) using micro push-out test. For this purpose were selected thirty bovine teeth of similar. Results in general, considering that evaluated three types of failure adhesive, mixed and cohesive concludesthat the cement Rely X U100 showed better adhesion than the cement Ketac-Cem (p≤0,05). and that the dominant failure mode of this cement was the adhesive and cement Ketac Cem showed a predominantly mixed fracture mode. cohesive ype of failures were not found.